(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Cancer is the uncontrolled growth and spread of abnormal cells, associated with regulation of cell cycle and apoptosis. Plant-derived compound is now considered as the most effective method of cancer treatment. The focus of the current research has been based on the identification of natural and synthetic compound that can be used in the prevention or the treatment of cancer. Methanolic extract of Rhizophora mucronata showed the presence of carbohydrates, phenol, alkaloid, amino acids, fat, flavonoids, glycosides, phenols, protein, saponins, sterols and tannins. Fourier-transform infrared spectroscopy (FTIR) confirmed the presence of primary, secondary amines, amides, alkanes, alkynes, aldehydes, saturated aliphatic, primary amines, alkyl halides, aliphatic amines, carboxylic acids, alkyl halides and alkyne. In 3-(4,5- Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay, at the concentration of 100 µg/mL of the extract, the viability of the cells was 90%. When increasing the concentration of the extract, the viability of the cells was decreased. At the concentration of 1,000 µg/mL, the viability of the cells was 50%. Tryphan blue dye exclusion assay was carried to perform the test for cell viability of the half maximal inhibitory concentration (IC50) (1,000 µg/mL) value was found in the extract. The percentage of viability of Michigan Cancer Foundation-7 (MCF-7) cell line for control is 100%. Based on the result of present study, it can also be concluded that the effect on methanolic extract of R. mucronata has the anticancer activity potential in MCF-7 cell line.